2006
DOI: 10.1001/archinte.166.2.231
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase Type 5 Inhibition Is a Novel Therapeutic Option in Raynaud Disease

Abstract: Our data indicate that phosphodiesterase type 5 inhibition significantly improves peripheral blood flow and clinical symptoms in a large subset of patients with RD and, thus, may provide a novel therapeutic approach in such individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 20 publications
1
48
0
3
Order By: Relevance
“…E) OTHER POTENTIAL USES. Other possibilities for use of PDE5 inhibitors include treatment of Raynaud's disease (54,86,118), suppression of other autoimmune diseases (48, 343), and relief of symptoms associated with cystic fibrosis (67,222,223). Potential treatment of genitourinary tract dysfunctions (benign prostate syndrome, overactive bladder, and urge incontinence) has garnered a lot of attention (324,325,362,397,425), as has treatment of Peyronie's disease (128), premature ejaculation, and ureteral relaxation for passage of kidney stones (132,325).…”
Section: Expanded Uses For Approved Pde5 Inhibitorsmentioning
confidence: 99%
“…E) OTHER POTENTIAL USES. Other possibilities for use of PDE5 inhibitors include treatment of Raynaud's disease (54,86,118), suppression of other autoimmune diseases (48, 343), and relief of symptoms associated with cystic fibrosis (67,222,223). Potential treatment of genitourinary tract dysfunctions (benign prostate syndrome, overactive bladder, and urge incontinence) has garnered a lot of attention (324,325,362,397,425), as has treatment of Peyronie's disease (128), premature ejaculation, and ureteral relaxation for passage of kidney stones (132,325).…”
Section: Expanded Uses For Approved Pde5 Inhibitorsmentioning
confidence: 99%
“…In addition, the oral formulation of iloprost did not show a benefit over placebo in the treatment of RP (23). Phosphodiesterase V inhibition may be useful for the treatment of RP, but further studies are necessary (24,25). Treatment with sildenafil was shown to improve the RCS by 27% compared with placebo in a small crossover study of 18 patients (16 with secondary RP and 2 with primary RP) (25).…”
Section: Discussionmentioning
confidence: 99%
“…Raynaud's disease is characterized by painful temperature-sensitive, digital vasospasms leading to pale, cyanotic skin mostly limited to the digits (Pope 2007). In several clinical studies, sildenafil and vardenafil have been shown to improve peripheral blood flow, decrease the severity of clinical symptoms, and reduce the frequency and cumulative attack duration in some Raynaud's patients (Caglayan et al 2006;Fries et al 2005).…”
Section: Raynaud's Diseasementioning
confidence: 99%